(untitled) (Italian Journal of Public Health, 2012)
Background: although the epidemiological features of overweight and obesity have been well described, especially for very populous urban areas, less evidences are available for small urban areas. The aim of the present work was to assess BMI and factors associated with overweight and obesity in a representative sample of general population of a small city of Western Sicily (Italy). Methods: four hundred and eleven randomly selected adult subjects from general population living in a small Sicilian city with 7 144 inhabitants were interviewed by a standardized questionnaire investigating life-styles, eating habits, anthropometric measurements (weight, height and BMI) and socio-economic deprivation. Results: the standardized prevalence of overweight and obesity were 43.8% and 18.3%, respectively. The multivariate analysis has indicated an increased risk of BMI≥25 in subjects 40-59 years old (OR=2.3; 95% CI=1.2-4.4) in comparison with 18-39 years old, in males (OR=2.8; 95% CI=1.6-4.7) in comparison with females, and in participants who had a higher socio-economic deprivation (OR=1.3; 95% CI=1.1-1.7). Conclusions: in small urban areas some demographic factors and socio-economic deprivation can be considered important risk factors for increased BMI also after controlling for the most common confounding factors.